2013
DOI: 10.1371/journal.ppat.1003459
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Cholesterol Modulates Pathogen Blocking by Wolbachia

Abstract: The bacterial endosymbiont Wolbachia pipientis protects its hosts from a range of pathogens by limiting their ability to form infections inside the insect. This “pathogen blocking” could be explained by innate immune priming by the symbiont, competition for host-derived resources between pathogens and Wolbachia, or the direct modification of the cell or cellular environment by Wolbachia. Recent comparative work in Drosophila and the mosquito Aedes aegypti has shown that an immune response is not required for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
239
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 258 publications
(247 citation statements)
references
References 44 publications
5
239
1
2
Order By: Relevance
“…There is evidence that multiple host mechanisms may be involved in inhibiting viral replication including synthesis of reactive oxygen and cholesterol and induction of host autophagy (Le Clec'h et al 2012;Pan et al 2012;Caragata et al 2013;Wong et al 2015). Our finding that Wolbachia dramatically alters host ER morphology and relies on the ERAD pathway to maintain titer suggests the involvement of a previously unsuspected mechanism in preventing the replication of positive-strand RNA viruses.…”
Section: Discussionmentioning
confidence: 77%
“…There is evidence that multiple host mechanisms may be involved in inhibiting viral replication including synthesis of reactive oxygen and cholesterol and induction of host autophagy (Le Clec'h et al 2012;Pan et al 2012;Caragata et al 2013;Wong et al 2015). Our finding that Wolbachia dramatically alters host ER morphology and relies on the ERAD pathway to maintain titer suggests the involvement of a previously unsuspected mechanism in preventing the replication of positive-strand RNA viruses.…”
Section: Discussionmentioning
confidence: 77%
“…Two recent studies support this notion: Wolbachia and Drosophila C virus compete for cholesterol, resulting in a delay in virus-induced mortality for Wolbachia-infected flies (40), and upregulation of an A. aegypti methyltransferase gene by Wolbachia contributes to dengue virus inhibition (41). These results are important in an applied context of utilizing Wolbachia infections for dengue virus control.…”
mentioning
confidence: 77%
“…(2016) and Caragata et al. (2013) who demonstrated that larval nutrition and adult carbohydrate intake did not affect DENV infection rates in w Mel mosquitoes. Temperature, in contrast, has been shown to determine whether the w AlbB Wolbachia strain inhibits, enhances, or has a neutral effect on oocyte infection rate and intensity of Plasmodium yoelii in An.…”
Section: Discussionmentioning
confidence: 99%